Platelet-rich fibrin membrane associated with the coronal replacement flap three years later - Lázaro Sarduy Bermúdez; Olga Lidia Véliz Concepción; Felisa Veitia Cabarrocas; Manuel Antonio Arce González; Eligio Eduardo Barreto Fiu; Marysol Rodríguez Felipe (Medisur)
Foundation: the association of the platelet-rich fibrin membrane with the coronal replacement flap constitutes a modality of tissue engineering that provides regenerative elements to the tissue repair process. Objective: to evaluate the effectiveness of the platelet-rich fibrin membrane associated with the coronal repositioning flap in the treatment of periodontal recession three years later. Methods: a quasi-experiment was carried out at the Villa Clara Dentistry Faculty, from March 2017 to July 2020, a study population of 46 patients with periodontal recession, who required root coverage using the replacement flap coronal. Intentional non-probabilistic sampling by criteria was used, and the sample of 26 patients. Study sites and control sites were established. The studied variables were: age, sex, recession length, Miller classification, root coverage, width and gain of the attached gingiva, evaluation categories and treatment effectiveness. Results: in 88.68% of the teeth located in the study sites, the favorable evaluation category predominated. The effectiveness percentage three years after treatment was higher in the study sites (54.71%). Conclusions: the treatment of periodontal recession with platelet-rich fibrin membrane associated with the coronal replacement flap was considered more effective three years after the procedure.